Cover Picture: Plasma Process. Polym. 8∕2014. Issue 8 (August 2014) - Mertz, Grégory; Fouquet, Thierry; Becker, Claude; Ziarelli, Fabio; Ruch, David
<x xml:space="preserve">Abstract</x> Front Cover: A difunctional precursor bearing an anhydride hydrolyzable function and two methacrylates groups was plasma polymerized by aerosol assisted atmospheric dielectric barrier discharge to produce a highly cross‐linked water sensitive coating. First results confirmed the good retention of the hydrolysable function as well as the hydrolytic degradation, achieved in about ten days under normal conditions. Further details can be found in the article by Grégory Mertz et. al. on page 728. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>